2006
DOI: 10.1002/app.24630
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics for simulation of processing of various polyesters

Abstract: The approach to determine crystallization kinetic parameters based on the DSC nonisothermal crystallization experiments is applied to poly(butylene terephthalate) (PBT) and poly(ethylene-2,6-naphthalate) (PEN). The differential form of the Nakamura equation and master curve approach are used. The isothermal induction times are obtained from nonisothermal induction times according to the concept of induction time index. The correction of temperature lag between the DSC furnace and the sample is incorporated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
11
0
3
Order By: Relevance
“…It is known that the crystallization temperature depends on the cooling rate. Studies of the kinetics of crystallization for several types of thermoplastic polyesters were done to simulate the injection molding 29 . It was found that the PBT crystallization temperature was drastically reduced when the cooling rate was increased.…”
Section: Capillary Rheometry Characterizationmentioning
confidence: 99%
“…It is known that the crystallization temperature depends on the cooling rate. Studies of the kinetics of crystallization for several types of thermoplastic polyesters were done to simulate the injection molding 29 . It was found that the PBT crystallization temperature was drastically reduced when the cooling rate was increased.…”
Section: Capillary Rheometry Characterizationmentioning
confidence: 99%
“…Entretanto, conforme esperado, a defasagem passa por um máximo durante o desenvolvimento do processo de cristalização, pois este é um fenômeno exotérmico que atrasa o resfriamento da amostra. Para a taxa de resfriamento de 40 K/min o pico de defasagem é de aproximadamente 3 K. Para uma amostra de polipropileno graftizado com ácido acrílico, Carvalho e Bretas [9] determinaram uma defasagem máxima de 7 K, de modo similar ao verificado por Isayev [20] para amostra de polibutileno tereftalato (PBT) nesta mesma taxa de resfriamento. Já para uma amostra de outro poliéster (polietileno-2,6 naftalato -PEN), Isayev [20] encontrou pico de defasagem de 3 K, como observado no presente trabalho para a poliamida 66 a 40 K/min.…”
Section: Resultados E Discussõesunclassified
“…Para a taxa de resfriamento de 40 K/min o pico de defasagem é de aproximadamente 3 K. Para uma amostra de polipropileno graftizado com ácido acrílico, Carvalho e Bretas [9] determinaram uma defasagem máxima de 7 K, de modo similar ao verificado por Isayev [20] para amostra de polibutileno tereftalato (PBT) nesta mesma taxa de resfriamento. Já para uma amostra de outro poliéster (polietileno-2,6 naftalato -PEN), Isayev [20] encontrou pico de defasagem de 3 K, como observado no presente trabalho para a poliamida 66 a 40 K/min. Diferenças nestes valores se explicam em virtude do maior calor de cristalização, da massa utilizada no ensaio e na própria cinética de cristalização.…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…Using the calculated K(T) and assuming n equal to 3, the differential form of the Nakamura equation 10 , given by Equation 7, can be used to simulate the dθ/dt vs. T curves, which are integrated to obtain almost exclusively to the Nakamura equation, mostly in Isayev's various scientific works [6][7][8][9] . In this respect, nonlinear regression is more flexible; moreover, it can be applied to other types of equation, not only to those that fit into the form of Equation 1.…”
Section: Abstract: Master Curve Approach Non-isothermal Crystallizatmentioning
confidence: 99%